Performa Sensor Berbasis Magneto-Impedansi pada Multilapisan [Ni80Fe20/Cu]N: Blasius Anggit Wicaksono, Nuryani, Budi Purnama - Blasius Anggit Wicaksono, Blasius Anggit Wicaksono; Nuryani, Nuryani; Budi Purnama, Budi Purnama (Jurnal Fisika dan Aplikasinya, 2025)
Analysis of performance magnetic sensor has been carried out based magneto-impedance of [Ni80Fe20/Cu]N multilayers on Cu wire. The multilayer is the result of electro-deposition methods with Pt (platinum) as the electrode. Sensor performance observed from the measurement of magneto-impedance ratio and sensitivity of the sample. While the sensor is modified based on the thickness of the conductor layer, the number of repetition in multilayer systems and a shape of geometric sensor. The observation shows that the highest MI sensor sensitivity is 53.75% / mT to sample of [Ni80Fe20 (800nm)/Cu (200nm)]3.